Beneath the kiln: The unyielding spirit of women shaping rural India's brick tale - Prosenjit Kayal; Indrajit Roy Chowdhury (Societal Impacts)
The brick industry, characterized as an informal and unorganized sector in India, has witnessed growth concurrent with urbanization across various states. This labor-intensive industry relies significantly on the widespread exploitation of women and children and heavily depends on migrant workers for production. This study aims to shed light on the current socio-economic conditions of women in the brick industries of Falta and Budge Budge-II C.D blocks in the South 24 Parganas District of Indian state West Bengal. The variables considered for this study encompass gender, age, marital status, nature of work, experience, education, income, benefits, and challenges —these factors serve as indicators of the socio-economic status of women in these manufacturing units. Environmentalists have identified the brick industry as one of the hazardous sectors with adverse implications for the health and physiological well-being of women and children. The present study is based on both primary and secondary data. The findings reveal that women in this field experience various forms of suffering, and the prevalence of child labor is notably high for both boys and girls in the brick kilns of these two blocks.